Roux-en-Y: the route to successful long-term jejunal feeding. (4th April 2011) - Paxton, C E; Gillett, P M; Wilkinson, A G; McGurk, S; Livingstone, J; Mitchell, D J; Devadason, D A; Munro, F D; Wilson, D C
Abstract : Background and aim: Increasing numbers of children with marked upper Gastrointestinal (GI) dysmotility require home enteral tube feeding (HETF). We reviewed the need and outcome of medium/long-term jejunal feeding for problematic gastric HETF. Methods: Retrospective cohort study (database and clinical note review) of use of polyethylene glycol (PEG)-J, transgastric gastrojejunostomy (GJ) tubes and surgical roux-en-Y jejunostomy (ReYJ) in a regional centre serving 1.25 million people. Nasojejunal feeding tubes had only short-term use as a guide to need for jejunal route. All children receiving HETF under 18 years of age during 1 January 2002 to 30 September 2010 were included. Results: 795 children received HETF during the study period. 33 (4%) required medium/long-term jejunal feeding – PEG-J tube in 4, GJ tube in 25, initial surgical ReYJ in 4. 25 children had 71 GJ tubes placed endoscopically/radiologically. The one major complication was death following small bowel intussusception. 43 of 71 tubes were changed for minor complications, including burst balloons in 16 (37%), holes in the Y-port/tube in 10 (23%), and fungal infection in 4 (9%). Proximal tube migration was problematic with both GJ and PEG-J tubes. Of the 29 PEG-J or GJ tube fed children, 7 (24%) returned to gastric feeding, 5 (17%) died from underlying neurodisability and 8 (27%) continue with GJ/PEG-J, 2 awaiting formation of ReYJ. The remaining 9 (31%) needed long-term jejunal feeding and had a surgical ReYJ formed. 13 children had ReYJ formation, at a median (range) age of 3 years 4 months (7 months–17 years 10 months). 11 (85%) of these children have underlying neurodisability, and seven (53%) had previous fundoplication. In terms of outcomes, nine (69%) continue with only minor stoma infection and leakage, two (15%) died from underlying condition, one (8%) moved from region and one (8%) transitioned successfully to adult services. Conclusions: Medium to long-term jejunal feeding via PEG-J or GJ tubes to children with severe GI dysmotility is used for problematic HETF, albeit with time-consuming practical challenges, particularly urgent tube changes. Surgical ReYJ formation provides a secure, relatively complication-free means of providing long-term jejunal feeding to these children.